Cold Hardiness of Terrestrial Mites at Signy Island, Maritime Antarctic - Block, William; Sømme, Lauritz (Oikos, 1982)
The cold hardiness of four species was studied in respect of supercooling ability, cryoprotective substances, chill-coma temperatures and survival under anaerobiosis. The effects of low temperature acclimation and starvation on cold hardiness were examined experimentally. (2) Mean supercooling points of field animals ranged from -6.1° to -28.8°C during Jan-Mar 1980. In Nanorchestes antarcticus (Strandtmann) and Alaskozetes antarcticus (Michael), a bimodal distribution of individual supercooling points occurred with the low group (LG) consisting of animals without gut nucleators. In Stereotydeus villosus (Trouessart) and Gamasellus racovitzai (Trouessart) only a high group (HG) was present in the supercooling-point distributions. (3) In all species, except the predatory G. racovitzai, starvation combined with low temperature exposure for various time periods lowered the mean supercooling point. This was associated with increased concentrations of glycerol in the body fluid. Glucose, ribitol and mannitol together with straight chain hydrocarbons were also detected in the extracts by GLC techniques. (4) Chill-coma temperatures varied from -4.5° to -8.0°C. (5) Under anoxia at 0°C, survival of A. antarcticus was greater than that of G. racovitzai, with the later nymphal stages being slightly more resistant than adults.
Publisher: [Nordic Society Oikos, Wiley]
Keywords: Antarktis; Sør-Orknøyene; entomologi; kuldetoleranse; midder; miter; virvelløse dyr

Norge i polarområdene - Egeland, Knut (Leif Holtedahls forl., 1982)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Nordmenn; Norge; Norsk Polarinstitutt; Peter I. Øy; Sørishavet; geografi; historie; norske ekspedisjoner; oppdagelsesreiser; polarområdene; polarpolitikk

Antarktis - Greve, Tim (Australia, Oceania og Antarktis, 1982)
Keywords: Antarktis; Antarktistraktaten; Sydpolsekspedisjonen; forskning; historie; hvalfangst; oppdagelsesreiser

Nye fossile virveldyr fra Antarktis - Heintz, Natascha (Naturen, 1982)
Keywords: Antarktis; fossiler; paleontologi

Tabular icebergs in ocean waves - Kristensen, Monica; Squire, Vernon A; Moore, Stuart C (Nature, 1982)
Keywords: Antarktis; bølger; ekspedisjoner; glasiologi; havet; isbreer

Supercooling and winter survival in terrestrial arthropods - Sømme, Lauritz (Comparative Biochemistry and Physiology Part A: Physiology, 1982)
Keywords: Antarktis; ekspedisjoner; forskning; kuldetoleranse; virvelløse dyr

Cold Hardiness of Collembola at Signy Island, Maritime Antarctic - Sømme, Lauritz; Block, William (Oikos, 1982)
The cold hardiness of two Antarctic species of Collembola, Cryptopygus antarcticus Willem and Parisotoma octooculata (Willem), was studied in field fresh, starved and low temperature acclimated specimens at Signy Island, in the South Orkney Islands. Supercooling points of both species clearly fell in a high group (HG) and a low group (LG) with a division at ca. -15°C. Field fresh specimens mainly had HG supercooling points, while starvation at 5° and 15°C greatly increased the number of LG animals. Further evidence of the relation between supercooling and feeding status was obtained in C. antarcticus. Specimens fed moss turf homogenate almost entirely returned to HG supercooling points, indicating the presence of efficient nucleators in this substrate. In specimens fed purified green algae a high proportion of LG supercooling points was retained, which suggests a lack of nucleators in this kind of food. Increased ability of LG specimens to supercool was demonstrated in C. antarcticus following acclimation at -5°C, and in P. octooculata at 0°C. In C. antarcticus an increase in concentrations of cryoprotective substances took place at -5°C concurrent with the lowering of the mean supercooling point. The main substances of the multicomponent cryoprotectant system of this species were trehalose, mannitol and glycerol. Chill-coma temperatures of specimens collected in the field differed in C. antarcticus and P. octooculata with mean values of -8.3° and -4.8°C, respectively. P. octooculata was less resistant to anaerobic conditions than C. antarcticus. All specimens of the former species were killed within 8 d in nitrogen at 0°C, while ca. 30% of C. antarcticus specimens survived after 28 d.
Publisher: [Nordic Society Oikos, Wiley]
Keywords: Antarktis; Sør-Orknøyene; entomologi; kuldetoleranse; leddyr; virvelløse dyr